Effectiveness of Bagea Sago Date Cake Against Weight Gain Infants Aged 6-12 Months - Luciana Heidee Christianty; Mardiana Ahmad; A. Nilawati Usman; A.Wardihan Sinrang; Aryadi Arsyad; St. Raf’iah (Syntax Literate, 2022)
Objective: This study aims to assess the effectiveness of giving Bagea Sago date cakes in increasing the weight of children aged 6-12 months. Method: The design of the study used queasy experiments with a pretest and post-test approach with a control group. The study sample was 40 babies aged 6-12 months. The samples were divided into two groups, namely the intervention group (20 children), who were given date Sago Bagea cakes and the control group (20 children) who were given Sago Bagea cakes. The research begins with weighing weight before the intervention is carried out. Purposive sampling according to predetermined criteria. The instrument used was in the form of a questionnaire used to assess the BB of the body of children aged 6-12 months as well as observation sheets to control the administration and ascertain whether respondents consumed the date Sago Bagea cake given. Data analysis using t paired test and t independent test. Results: In the mean±SD intervention group, the body weight before treatment was 7.6±0.995 kg, and after the intervention, there was a weight gain with a mean±SD of 8.36±0. 811 kg. For the control group, the mean±SD body weight before treatment was 7.36±1,140 kg, while at the time± of post±SD weight gain was 7. 48±1. 141 kg. The results of the bivariate analysis showed that there was a difference in body weight in the group that received the intervention in giving date Sago Bagea cake with a value of p = 0.015< 0.05. Conclusion: Bagea Sago date cake can be used as an alternative to complementary breast milk (Makanan Pend besides breast milk) in children aged 6-12 months.